Thermal and Electron Plasma Effects on Phase Separation Dynamics Induced by Ultrashort Laser Pulses - Maxime Cavillon; Jing Cao; Maxime Vallet; François Brisset; Léo Mazerolles; Brahim Dkhil; Matthieu Lancry; Bertrand Poumellec (Crystals, 2022)
During ultrafast laser-induced crystallization from glass with a non-congruent composition, a phase separation occurs. The morphology of the crystallized area, inside the heat-affected zone (HAZ), is spectacular showing a bouquet-like structure, under some specific conditions related to glass chemical composition and laser parameters. In this work, we investigate this HAZ along a written line through a set of high-resolution electron microscopy techniques to probe both the morphology and the chemical distribution at the nanoscale. Based on these findings, we demonstrate that the bouquet-like structure arises from poorly textured nanocrystals between two regions that have probably accumulated elastic strain. From that analysis, we also provide insights into the chemical separation process during this complex light-matter transformation in which the induced plasma structure guides the spatial distribution of SiO2 and LiNbO3. We suggest a model based on an electric field modulation produced by the inhomogeneous plasma electron trapping, that modifies the electrochemical potentials of the constituents.